Factors Associated with Safe Sex Behavior Among Commercial Sex Workers in Banjarsari, Surakarta, Central Java - Maecelina Hestin Ambarsari; Argyo Demartoto; C.S.P Wekadigunawan (Masters Program in Public Health, 2018)
Background: It is estimated that more than one million people in the world contract sexually-transmitted disease everyday. Annually approximately 357 million new infections occur by one of four sexually-transmitted diseases: chlamidia, gonorrhea, syphilis, and mouth ulcer. To date HIV/AIDS has spread in 407 of 507 districts and municipalities in Indonesia, or equivalently covering 80% districts and municipalities of the country. In Surakarta, the cumulative incidence of HIV/AIDS from 2005 to 2017 was 561 cases, with 38 HIV cases and 46 AIDS cases in 2017 alone. The incidence of HIV/AIDS has been increasing year by year. This study aimed to examine factors associated with safe sex behavior among commercial sex workers in Banjarsari, Surakarta, Central Java.Subjects and Method: This was an analytic observational study with cross-sectional design. The study was conducted in Banjarsari Sub-district, Surakarta, Central Java. A total sample of 100 commercial sex workers was selected by stratified random sampling. The dependent variable was safe sex behavior. The independent variables were knowledge of infectious transmitted disease and HIV/AIDS, self efficacy, condom availability, access to health care service, health personnel support, and peer support. The data were collected by questionnaire and analyzed by multiple linear regression.Results: Safe sex behavior was associated with good knowledge of sexually-transmitted disease and HIV/AIDS (b=0.19; 95% CI=0.01 to 0.30; p=0.032), strong self efficacy (b= 0.18; 95% CI= 0.01 to 0.38; p= 0.047), condom availability (b=0.30; 95% CI= 0.36 to 1.20; p<0.001), good access to health care service (b= 0.19; 95% CI= 0.02 to 0.52; p= 0.035), strong health personnel support (b= 0.18; 95% CI= 0.01 to 0.57; p=0.041), strong peer support (b= 0.17; 95% CI= 0.01 to 0.50; p= 0.046).Conclusion: Safe sex behavior is associated with good knowledge of sexually-transmitted disease and HIV/AIDS, strong self efficacy, condom availability, access to health care service, strong health personnel support, strong peer support.Keyword: safe sex behavior, knowledge, self efficacy, condom availability, access to health service, health personnel support, peer supportCorrespondence: Maecelina Hestin Ambarsari. Masters Program in Public Heath, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: hestinmaecelina@gmail.com. Mobile: +6285742975078.Journal of Epidemiology and Public Health (2018), 3(1): 60-71https://doi.org/10.26911/jepublichealth.2018.03.01.05